Computationally Exploring and Alleviating the Kinetic Bottlenecks of Anaerobic Methane Oxidation - Grisewood, Matthew J.; Ferry, James G.; Maranas, Costas D. (Frontiers in Environmental Science, 2018)
The anaerobic oxidation of methane by methanotrophic archaea offers a carbon- and electron- efficient route for the production of acetate, which can be further processed to yield liquid fuels. This acetate production pathway is initiated by methyl-coenzyme M reductase, but this enzyme can only oxidize trace amounts of methane ex situ. Efforts to improve the kinetics of methyl-coenzyme M reductase through enzyme engineering have been, in part, limited by low-throughput assays. Computational enzyme engineering can circumvent this limitation through the design of smaller, more focused libraries, which have a higher probability of success. By drawing from a new consensus reaction mechanism for Mcr and newly published data, the first complete kinetic characterization of the Mcr reaction mechanism is proposed. In the developed kinetic description, the rate of methyl-coenzyme M unbinding is proposed to limit Mcr overall kinetics. A revised computational method was devised to improve the rate of product release while not disrupting the reaction’s activated complex. Large, hydrophobic amino acids that can assume multiple conformations were predicted to be most effective at reaching this design goal. Other rate-limiting scenarios were examined, such as (i) high-temperature (> 45 °C), (ii) methyltransferase-limiting case, and (iii) ineffective Cofactor F430 binding. A separate library of designs is put forth for each one of these cases. These efforts mark the first computational attempt at redesigning methyl-coenzyme M reductase for reversed or improved activity, which if experimentally validated, would have a cross-cutting impact across the biotechnology and biochemistry fields by debottlenecking anaerobic methane oxidation.